2016
DOI: 10.1080/02726351.2016.1211778
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of ball-milled metal matrix nanocomposites (Cr, Ni, Ti)-25 wt% (Al2O3np, SiCnp)

Abstract: The microstructure of high-temperature metals such as Ti, Ni, and Cr can be modified using ceramic nanoparticles to form metal matrix nanocomposites (MMNCs). Such materials are generally prepared via powder metallurgy routes. In this study, 25 wt. % SiCnp and Al2O3np were separately ball-milled as a reinforcement of Ti, Cr, and Ni matrices to investigate their effects on the phase formation and morphology of the MMNCs. The XRD, SEM, and FESEM results indicated that the alumina-metal system could not be thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 75 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…The submicrometer particles of alumina are considered incoherent precipitates that can inhibit the grain growth during the thermal treatment, when located in the grain boundaries 9,21,22 . In general, the authors [10][11][12][16][17][18][19] also observed that, increasing the milling times, the properties of the MMCs composed by a metallic matrix and alumina as reinforcement achieved better results of density, porosity, hardness and elastic modulus, due to the factors discussed during this work.…”
Section: Sintered Samples Analysissupporting
confidence: 53%
See 2 more Smart Citations
“…The submicrometer particles of alumina are considered incoherent precipitates that can inhibit the grain growth during the thermal treatment, when located in the grain boundaries 9,21,22 . In general, the authors [10][11][12][16][17][18][19] also observed that, increasing the milling times, the properties of the MMCs composed by a metallic matrix and alumina as reinforcement achieved better results of density, porosity, hardness and elastic modulus, due to the factors discussed during this work.…”
Section: Sintered Samples Analysissupporting
confidence: 53%
“…It happens due to the small percentage of alumina that was added to the powder. Other authors as [10][11][12]16,18,19 also investigated the effect that extending the milling times generates in the crystalline structure of MMCs composed by metallic powders and alumina. The studies attested that, by increasing the milling times, the amorphization phenomena continued to happens.…”
Section: Powders Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the increased amount of cold working, the number of crystal defects (dislocation, vacancies, grain boundaries, stacking faults, etc.) increases with time and thus diffusivity of solute elements increases [38]. This leads to an increment in the defects and dislocations density which reduces the activation energy for diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Ball milling process is a typical combination of physical and chemical method to prepare nanothermites, in which particle sizes are affected by mechanical forces, and thus becomes a facile, cost‐effective and massive productive method. So far, massive researchers have applied this method on the mixing of aluminum and metal oxides.…”
Section: Introductionmentioning
confidence: 99%